A 10-year cohort on prognostic outcomes in patients presenting with acute myocardial infarction complicated by cardiogenic shock and/or cardiac arrest. (3rd October 2022) - Chew, N; Teo, V; Tan, C; Kong, G; Chin, Y H; Ambhore, A; Low, A; Lee, C H; Chan, M Y; Tan, H C; Ph, L O H
Abstract: Background: Cardiogenic shock (CS) and cardiac arrest (CA) complicating acute myocardial infarction (AMI) portend unfavourable outcomes. This study examined the prognosis of patients presenting with AMI complicated by CS and/or CA. Methods: Consecutive patients presented with AMI to a percutaneous coronary intervention-capable tertiary institution between 2011 and 2021 were studied. Patients were stratified based on the presence or absence of CS (CS+ or CS−) and CA (CA+ or CA−). The primary outcome was 30-day cardiovascular-related mortality. Subgroup analyses based on AMI-type and sex were conducted. Kaplan-Meier curves for cardiovascular-related mortality based on the AMI-type and sex were constructed. Results: The study included 11, 608 AMI patients, 283 of whom had CS+/CA+, 1, 068 had CS+/CA−, 54 had CS−/CA+ and 10, 203 had CS−/CA−. Cardiovascular-related mortality was significantly higher for CS+/CA+ (57.6%), followed by CS+/CA− (41.6%), CS−/CA+ (20.4%) and CS−/CA− (2.4%). Kaplan-Meier curves demonstrated CS+/CA+ group had the highest mortality (HR=36.26; 95% CI: 29.71–44.25, p<0.001), followed by CS+/CA− (HR=21.59; 95% CI: 18.47–25.24, p<0.001) and CS−/CA+ (HR=9.18; 95% CI: 5.02–16.80, p<0.001), with CS−/CA− as the reference. Those with NSTEMI had consistently higher cardiovascular-related mortality rates than their STEMI counterparts for all groups, apart from the CS+/CA+ group. The sex-specific analysis demonstrated that the survival curves for females with CS+/CA+, CS+/CA− and CS−/CA+ converged, whilst the survival curves for males diverged over time. The multivariable Cox regression revealed the presence of CS and CA are independent predictors of cardiovascular-related mortality, but not NSTEMI, when adjusted for age, gender, diabetes, left ventricular ejection fraction, chronic renal failure, and culprit vessel. Conclusions: AMI associated with CA and CS portends the least favourable survival, followed by those with CS or CA alone. Excess mortality was observed in the traditionally perceived lower-risk groups, particularly in women. This calls for increased awareness amongst clinicians when managing this subset of high-risk patients. Funding Acknowledgement: Type of funding sources: None.